Vegetation differentiation and secondary succession on abandoned agricultural large-areas in south-eastern Poland - Barabasz-Krasny, Beata (Biodiversity: Research and Conservation, 2016)
In Poland, the largest stretches of abandoned agricultural areas were formed at the end of the 1980s, along western and eastern borders, among others, in Przemyśl Foothills (Pogórze Przemyskie). Therefore, the research on the diversity of plant communities from abandoned agricultural areas as well as main directions and the rate of succession after the cessation of management was undertaken in the vicinity of twelve municipalities in south-eastern Poland. This research revealed that the dominating direction of changes of the abandoned agricultural area vegetation was vanishing of plant groups with segetal and meadow species and spreading of shrub communities. A general increase in the forestation rate of the researched abandoned agricultural areas from 10-40% of the area in 1970-1971 to about 30-70% in 2003-2004 may be the evidence of the occurrence intensity of those phenomena.